Maternal Characteristics, Malnutrition, and Pregnancy Complications with the Incidence of Low Birth Weight in an Industrial Environment - Yulia Nur Khayati; Tandiyo Rahayu; Oktia Woro Kasmini Handayani; Evi Widowati; Dina Nur Anggraini Ningrum (Universitas Negeri Semarang in collaboration with Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI Tingkat Pusat) and Jejaring Nasional Pendidikan Kesehatan (JNPK), 2025)
Low Birth Weight is one of the leading causes of under-five deaths during the neonatal period. In Indonesia, the infant mortality rate is in the top 7 in the world. The industrial environment, where air pollution is high, is one of the factors causing LBW. The study aimed to identify the factors that influence the incidence of LBW in an industrial environment. Using data from a cohort of pregnant women in 2023, the study used a nested case-control design at Bergas Community Health Centre. The study population included all mothers who delivered live infants in 2023, totalling 832 respondents. Data from the study were analysed using Chi-Square for bivariate analysis and logistic regression for multivariate analysis. The results showed a relationship between maternal age, parity, maternal nutritional status, hypertension, preeclampsia, and anaemia with the occurrence of LBW with p < 0.0001. The multivariate analysis indicated a significant relationship between maternal age (OR 3.233, 95% CI 1.557 – 6.714), parity (OR 2.567, 95% CI 1.382 – 4.767), maternal nutritional status (OR 7.905, 95% CI 3.472 – 17.998), preeclampsia (OR 28.090, 95% CI 9.894 – 84.468), and maternal hemoglobin levels (OR 10.883, 95% CI 5.736 – 20.649) with the incidence of LBW. The most influential factor in LBW is the occurrence of preeclampsia in mothers.